2005
DOI: 10.1007/s00216-005-3123-6
|View full text |Cite
|
Sign up to set email alerts
|

Detector for particulate polycyclic aromatic hydrocarbons in water

Abstract: It is estimated that most polycyclic aromatic hydrocarbons (PAHs) in environmental water are not dissolved but rather in particulate form. Nevertheless, the currently available optical detectors are not suited for proper sampling of solid PAHs. A new setup for direct sampling and quantification of suspended particulate PAHs in water is suggested. It is based on a polymeric film that has the capability of dissolving PAH particulates, coupled to a traditional laser-induced fluorescence probe. Kinetics and perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…This could be attributed to differences in physical properties of Zn as compared to Cu and similar observations were made previously with ns LA. 42,43 The species expansion trends were the same for both Zn and Cu at various pressures. Since Zn always moves faster than Cu and is present in the plume front, Zn data was used as representative data for brass plume expansion for fitting drag or blast models.…”
Section: Resultsmentioning
confidence: 82%
“…This could be attributed to differences in physical properties of Zn as compared to Cu and similar observations were made previously with ns LA. 42,43 The species expansion trends were the same for both Zn and Cu at various pressures. Since Zn always moves faster than Cu and is present in the plume front, Zn data was used as representative data for brass plume expansion for fitting drag or blast models.…”
Section: Resultsmentioning
confidence: 82%
“…It is confirmed that the long-term exposure to these chemicals will induce health problems including cancer, transgenation and deformity. So far, sixteen kinds of PAHs have been identified as priority pollutants by the US EPA [1,2]. Meanwhile, a lot of analytical techniques have been developed to recognize and monitor these PAHs effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their ubiquitous nature, hydrophobic organic compounds such as polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) have been identified as environmental contaminants in almost every compartment of the global system (ATSDR, 2009). As byproducts of incomplete combustion of organic compounds, pyrosynthesis or pyrolysis of hydrocarbons, PAHs are released to the environment by both natural and anthropogenic sources (Levinson et al, 2008). PAHs may also reach water systems through oil spills and direct industrial effluent discharges.…”
Section: Introductionmentioning
confidence: 99%